PAKISTANI TEACHERS' PROFESSIONAL LEARNING EXPERIENCES: COMPARING FACE-TO-FACE VERSUS ONLINE LEARNING - Khan, Asma (TEFLIN Journal, 2018)
This qualitative in-depth interview study investigated the experiences of Pakistani English teachers in an online community, English Companion Ning (ECN). The main purpose of the study was to investigate what ECN meant to these Pakistani teachers and how they found their professional learning experiences different in ECN from face-to-face professional development programs in Pakistan. Data were gathered from six teachers through in-depth interviews, guided tours, field notes, memos, and ECN logs. Using the grounded theory approach, this study analyzed and interpreted the data through initial, focused, and axial coding. Data analysis revealed that being free from budget, temporal, and geographical constraints, the ECN provided numerous opportunities to the Pakistani teachers for a sustained and long-term professional learning in a collaborative setting.